Organizational competency toward the creation of Anti-violence Services - Passavanti, Domenica; Violi, Eliana; Zecca, Francesca (Quaderni di Psicologia Clinica, 2022)
The article describes a series of psychological interventions carried out in two anti-violence centers. The methodological hypothesis supporting the reporting frame is the organizational competency. The organizational competency is considered both as a construction of setting supporting the thinking of symbolic-emotional dynamics that organize a context, and a psychological-clinic competence within a psychoanalytic intervention. An interpretation of the problem is formulated based on the exploration of the cultural context of anti-violence centers. The examples how cased in the article describe how the organizational competency is declined as a competency to create services through interventions that aim at promoting a continual reflective process within the anti-violence centers.
Keywords: Anti-violence centers; client orientation; organizational competency; working group; gender based violence